The Importance of Selected Criteria for Assessing the Credibility of Information on the Internet from the Perspective of Users Searching Health and Disease Information Websites - Rusová, Jitka; Michková, Adéla; Pleskot, Ondřej; Podeszwa, Ondřej; Hlaváčková, Eva (Journal of Education Culture and Society, 2022)
Aim. The aim of the survey was to find out how and why users of websites containing health information searched for information, how they feel about selected criteria for assessing the credibility of information, and what they are more likely to trust when they encounter a discrepancy between information from the website and from a doctor.Methods. An online survey of users of 4 health information websites, two of which are listed as trusted sites on MedLike. The respondents assessed 10 criteria for determining the trustworthiness of online information and websites by assigning a number of stars (5 stars = important).Results. The questionnaire was answered by 32,428 respondents (79.5% women, average age 47 years). The most frequently cited reasons for seeking information were their own health or illness (49%). Most respondents searched for information through an Internet search engine (66%). The importance of the criteria for selecting information did not differ significantly. The respondents gave the highest score (2.29) to the criterion of ease (I can easily find what I need). This was followed by consistency with information from the doctor (2.28).Conclusion. The respondents searched for information in the way described in the literature as most common (using a search engine) and tended towards a heuristic evaluation of online information and its sources (ease of information retrieval) and also appreciated if the information found concurred with information from a healthcare professional.